Herbicide use history and perspective in South America - Merotto, Aldo; Gazziero, Dionisio L. P.; Oliveira, Maxwel C.; Scursoni, Julio; Garcia, Milton Alejandro; Figueroa, Rodrigo; Turra, Guilherme M. (Advances in Weed Science, 2022)
BackgroundAgriculture in South America (SA) had a great expansion in the last decades and weed control changed accordingly with region and crop practices.ObjectiveThe objective of this review is to present the history of herbicide use and discuss the main changes in weed management in SA.MethodsHerbicide use quantities were obtained from official institutions and commercial organizations in Argentina, Brazil, Chile, Paraguay and Uruguay. Data were summarized per active ingredient, herbicide mode of action or crop. The evolution of the cultivated area of the main crops in each country, and the crop and weed management associated to it were considered to discuss the importance and the consequences of the main herbicides used.ResultsIn 2019 the most used herbicides in Brazil were glyphosate, 2,4-D, atrazine, paraquat and diuron representing 62, 15, 7, 5 and 2% of the total amount used. In Argentina, the increasing selection of herbicide resistant populations (4 cases/year), resulted in utilization of older chemistries. Weed control in Uruguay is traditionally benefited from crop/pasture rotations but recently is also facing problems of continuous cropping systems. Agriculture in Chile is more diverse, but similar patterns and problems of herbicide use are present.ConclusionsIntensification of agriculture, no-tillage, glyphosate resistant crops, and herbicide resistant weeds were the most important drivers of herbicide use changes in SA. Integrated weed management is unpostponable to provide sustainable increasing food production in SA.